PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN METODE GAMES UNTUK MENINGKATKAN MOTIVASI BERPRESTASI SISWA KELAS X SMA NEGERI 14 PEKANBARU TP. 2015/2016 - Mustiqa '; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The success of students in learning process are really influenced by the achievement motivation. The low achievement motivationcan make students cannot reach the optimal learning result. In this case, schools, especially guidance teachers, are expected to have competences to do the action regarding the improvement of students’ achievement motivation. The objective of this research is to know the influence group guidance services by using games method in improving students’ achievement motivation on the experimental group. The method of this research is real-experimental method with the pattern of pre test-post test control group design. The subject of this research is 20 students of grade X SMA Negeri 14 Pekanbaru that have low achievement motivation. The technique of analyzing data applied three formula, Wilcoxon Experiment, Spearman Rank Experiment and Man Whitney Experiment. Based on the hypothesis experiment by applying SPSS 16.0, it is obtained that the value of sig. (2-tailed) is 0,117. Due to the fact that the value of sig. (2-tailed) more than the α value (0.117 > 0.05) thus it can be concluded that There is no positive impact that significant in giving group counseling services by using games method in improving students’ achievement motivation. The influence of group guidance services by using games method in order to improve students’ achievement motivation give contribution is 27,7%.Keywords: Group guidance services, Games Methods, achievement motivation